2023
DOI: 10.1085/jgp.202213206
|View full text |Cite
|
Sign up to set email alerts
|

The role of Zn2+ in shaping intracellular Ca2+ dynamics in the heart

Abstract: Increasing evidence suggests that Zn2+ acts as a second messenger capable of transducing extracellular stimuli into intracellular signaling events. The importance of Zn2+ as a signaling molecule in cardiovascular functioning is gaining traction. In the heart, Zn2+ plays important roles in excitation–contraction (EC) coupling, excitation–transcription coupling, and cardiac ventricular morphogenesis. Zn2+ homeostasis in cardiac tissue is tightly regulated through the action of a combination of transporters, buff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 203 publications
0
2
0
Order By: Relevance
“…An increase in MG23 expression and activity has been observed when cytosolic Zn 2+ levels rise [114]. This finding is supported by the presence of a common HxxE amino acid sequence conserved on Zrt-/Irt-like protein (ZIP) 1, 2, and 3, known as zinc transporters, where the Zn 2+ binding sites are located [115]. MG23, along with RyR2, adds more explanation on the diastolic SR Ca 2+ leakage.…”
Section: Crosstalk Between Mineralsmentioning
confidence: 83%
“…An increase in MG23 expression and activity has been observed when cytosolic Zn 2+ levels rise [114]. This finding is supported by the presence of a common HxxE amino acid sequence conserved on Zrt-/Irt-like protein (ZIP) 1, 2, and 3, known as zinc transporters, where the Zn 2+ binding sites are located [115]. MG23, along with RyR2, adds more explanation on the diastolic SR Ca 2+ leakage.…”
Section: Crosstalk Between Mineralsmentioning
confidence: 83%
“…It has been reported that low levels of Zn 2+ stimulate kinase activity, whereas high concentration of Zn 2+ inhibits the binding of Ca 2+ / calmodulin and inactivate the substrate phosphorylation activity of CaMPK-2. Moreover, Ca 2+ and Zn 2+ shape each other's intraneuronal dynamics (Dorward et al, 2023).…”
Section: Zinc As a Signaling Moleculementioning
confidence: 99%
“…Supra-physiological Zn 2+ concentration eventually caused dysrhythmia; however, bulk protein degradation was inhibited at Zn 2+ concentrations that caused no functional change. Although the exchange of intracellular and extracellular Zn 2+ is not directly linked to the contraction-relaxation cycle, internal Zn 2+ and Ca 2+ are reportedly interactive by competition for an ion channel (Dorward et al 2023 ). Increased extracellular Zn 2+ can be taken up by the heart beginning in minutes as revealed qualitatively by positron emission photometry (Firth et al 2022 ).…”
Section: Over-expression Of Web Proteases Might Require a Potent Dire...mentioning
confidence: 99%